Cost-utility of behavioural activation for mitigating psychological impacts of COVID-19 on socially isolated older adults with depression and multiple long-term conditions compared with usual care: results from a pragmatic randomised controlled trial - Simon Gilbody; Caroline Fairhurst; Catherine Hewitt; Dean McMillan; Carolyn Chew-Graham; Della Bailey; David Ekers; Steve Parrott; Elizabeth Littlewood; Peter Coventry; Han-I Wang; Kalpita Baird (BMJ Mental Health)
Background Depression alongside multiple long-term conditions (MLTCs) in older adults poses a critical public health challenge, worsening physical and mental health and increasing healthcare costs. COVID-19 restrictions further exacerbated these impacts. Behavioural activation (BA) shows promise as a remote intervention for depression during isolation, but its cost-effectiveness for depressed, socially isolated older adults remains uncertain.Objective This study aimed to assess the cost-utility of BA versus usual care for older adults with depression and MLTCs during COVID-19 restrictions.Methods A randomised controlled trial recruited and randomised individuals aged 65 and over with depressive symptoms and MLTC (n=435) to either the BA intervention or usual care. Costs were measured from the perspective of the National Health Service and personal social services. Quality-adjusted life years (QALYs) were measured using the EQ-5D-3L at baseline, and 1, 3 and 12 months postrandomisation. Incremental cost-effectiveness ratios were calculated, with uncertainty addressed through non-parametric bootstrapping. Sensitivity analyses were conducted to assess the robustness of the primary analysis.Findings Primary analysis indicated that BA generated a small cost-saving (£62.34 per older adult; 95% CI: −£120.44 to £239.70) while QALY improvements remained unchanged (0.007; 95% CI −0.036 to 0.022) compared with usual care. The probability of BA being the preferred option is 0.71. Sensitivity analyses supported the primary analysis findings, confirming their robustness.Conclusions and clinical implications Compared with usual care, BA demonstrated a slight cost reduction while maintaining QALY improvement. The findings provide promise for BA interventions for older people with depression and MLTCs facing isolation.